Flour moisture control for maximum water addition - Bontrager, Chad (Kansas State University, 2011)
This thesis examines flour moisture control and how this control can be an effective tool for cost minimization in a flour mill. Specifically, this thesis discusses the economic rationale behind the value of moisture control, the variables associated with moisture control, options for controlling those variables, the current control strategies, the decision process used to examine moisture control options, analysis of the solution, and implementation of optimal control strategies. In the area of optimal control strategies, two outcomes were generated in the thesis. The first outcome involved collecting data and developing a better understanding of the factors impacting flour moistures. The second outcome was to create a spreadsheet tool for use in the flour mill that would allow operators to determine an optimal water set point that would bring about a desired flour moisture taking into consideration the variables effecting flour moisture and their status at a given time. Both outcomes have been met and are outlined in detail in the thesis. It is understood that the conclusions of this thesis do not represent an end to the flour moisture control challenge and that more research is needed in order to implement further control measures. Work that remains to be done in order to achieve even better moisture control is also outlined in this thesis.
Keywords: Flour moisture control; Agriculture, General (0473); Food Science (0359)